Socket Preservation Using Platelet-Rich Fibrin and Free Gingival Grafts - Haya Hesham Abdel-Latif Afifi; Shaimaa Saieed Nasr; Munerah Saleh BinShabaib; Shatha Subhi Alharthi; Mona Shoeib (International Dental Journal)
ABSTRACT: Objective: The present randomised controlled trial is based on the null hypothesis that there is no difference in crestal bone levels (CBLs) following socket preservation (SP) using platelet-rich fibrin (PRF) and free gingival graft (FGG). The aim was to evaluate CBLs following SP using PRF and FGG. Methods: This study is a parallel-arm randomised controlled trial. Patients in the test and control groups underwent SP using PRF and FGG, respectively. Intraoral visual examination was performed to clinically assess signs of swelling, pus/abscess, and stability of sutures and graft. Self-rated postoperative pain was assessed after 1 week and 6 months using the visual analogue scale (VAS). At the 6-month follow-up, cone-beam computed tomography was performed to evaluate CBL in mesiodistal and buccolingual dimensions. The preoperative cone-beam computed tomographic images were superimposed with those taken at the 6-month follow-up to compare CBLs. Statistical comparisons were performed and level of significance was set at P < .05. Results: The test and control groups each comprised 13 individuals with comparable ages. All teeth included in the test and control groups were located in the maxillary aesthetic zone. At the 1-week follow-up, VAS scores were higher in the control than in the test group (P < .01). At the 6-month follow-up, none of the participants reported self-rated pain. The change in buccolingual dimension was greater in the control group than in the test group (P < .05). Conclusions: Both FGG and PRF are effective techniques for SP; however, the latter technique is more effcacious in maintaining buccolingual dimensions of the extraction socket.